Evaluation of pulse width modulation techniques to reduce total harmonic distortion in grid-connected PV systems - Adel, Bouledroua; Tarek, Mesbah; Samia, Kelaiaia (Institute of Advanced Engineering and Science, 2025)
The proliferation of grid-connected photovoltaic systems (GCPVs) has created significant challenges in maintaining power quality standards, particularly with respect to total harmonic distortion (THD). This research is concerned with evaluating three well-known pulse width modulation (PWM) techniques - sine PWM (SPWM), third harmonic injection PWM (THIPWM) and space vector PWM (SVPWM) for their effectiveness in mitigating THD in three-phase single stage GCPVs. Through extensive simulations performed in MATLAB/Simulink, a comprehensive comparative analysis is presented that reveals the strengths and limitations of each PWM strategy. The results show that SVPWM is the most effective technique for THD mitigation and outperforms its counterparts. THIPWM proves to be a promising second-best option, while SPWM lags behind in terms of harmonic suppression capabilities. This research not only quantifies the THD reduction achieved by each PWM technique but also delves into the underlying mechanisms and theoretical underpinnings that contribute to their distinct performances. The results are further supported by detailed harmonic spectrum analyses, providing valuable insights into the harmonic profiles associated with each modulation strategy.